Revisiting the colonial question in Latin America - Moraña, Mabel,; Jáuregui, Carlos A., (Iberoamericana ; Vervuert, 2008)
From the configuration of Empire in the colonial period to the multiple facets of modern coloniality, this book offers a challenging approach to the developments and effects of imperial domination and neocolonial rule in Latin America. Thought of as a contribution to current debates on postcolonialism and covering an ample range of topics, geocultural fields, and historical scenarios, Revisiting the Colonial Question in Latin America provides indispensable materials to the study of the formation and representation of colonial and modern subjectivities, the role of historical accounts, cultural practices, and symbolic representation (literary writing, oral narratives, visual images, and artifacts) through which some of the parameters of colonized epistemologies become apparent to the European Other.